1996
DOI: 10.1111/j.1469-8137.1996.tb04340.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular defence‐related root responses to invasion by arbuscular mycorrhizal fungi

Abstract: SUMMARYArbuscular mycorrhizal (AM) fungi, which date from the Devonian era, must have dealt ver\' earlj' on with problems of plant defence, a tactic which has enabled them to colonize roots of most extant plant taxa. Conversely, plants forming arbuscular mycorrhiza must exert some sort of control over the fungi during symbiotic interactions since mycelial proliferation within roots is confined to the cortical parenchyma tissue. Plants possess a panoply of defence mechanisms which are triggered by microbial att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(88 citation statements)
references
References 92 publications
2
85
0
1
Order By: Relevance
“…During the later steps of fungal colonization, chitin is ' naked ' and amorphous in the thin branches of arbuscules and can act as a potential source of elicitors. This hypothesis is supported by in situ hybridization experiments which have located transcripts of defence-related genes mainly in arbuscule-containing cells (Harrison & Dixon, 1994 ;Blee & Anderson, 1996 ;Gianinazzi-Pearson et al, 1996 ;Balestrini et al, 1997).…”
Section: Chitin Synthases In Fungal Growth and Morphogenesissupporting
confidence: 61%
“…During the later steps of fungal colonization, chitin is ' naked ' and amorphous in the thin branches of arbuscules and can act as a potential source of elicitors. This hypothesis is supported by in situ hybridization experiments which have located transcripts of defence-related genes mainly in arbuscule-containing cells (Harrison & Dixon, 1994 ;Blee & Anderson, 1996 ;Gianinazzi-Pearson et al, 1996 ;Balestrini et al, 1997).…”
Section: Chitin Synthases In Fungal Growth and Morphogenesissupporting
confidence: 61%
“…Intracellular fungal structures are separated from the plant cytoplasm by an extension of the plasma membrane, forming the periarbuscular membrane surrounding the arbuscule. The greatly increased surfaces of host and arbuscule plasma membranes offers optimized conditions for effective nutrient exchange via the established symbiotic interface (for review, see Gianinazzi-Pearson et al, 1996;Harrison, 1999).The exchange of phosphate via the periarbuscular interface and the induction of AM-specific phosphate transporters are already well characterized (Karandashov and Bucher, 2005;Requena, 2005). The same holds true for the regulation of AM by the phosphate availability for the plant.…”
mentioning
confidence: 76%
“…In some cases, an induction of defence responses was detected at early stages of root colonization followed by suppression at later stages of the symbiosis (Spanu et al, 1989 ;Lambais & Mehdy, 1993 ;Volpin et al, 1994Volpin et al, , 1995 ; in other cases, there was no major change in the expression of plant defence-related genes in response to mycorrhizal root colonization (Franken & Gna$ dinger, 1994 ;Blee & Anderson, 1996). The overall impression from these studies was that plant defencerelated genes are only weakly or transiently expressed in response to infection by AM fungi (for reviews, see Bonfante & Perotto (1995), Gianinazzi-Pearson et al (1996)). By contrast, numerous studies have demonstrated that, in pathogenic interactions, distinct changes in plant gene expression take place, many of which have presumed protective functions.…”
Section: mentioning
confidence: 98%
“…In other mycorrhizal systems, both stimulation and suppression of plant defence responses have been reported (for reviews, see Bonfante & Perotto (1995), Gianinazzi-Pearson et al (1996)). Early induction followed by suppression of plant defencegene expression has been demonstrated for mycorrhizal beans (Lambais & Mehdy, 1993).…”
Section: Mycorrhizal Colonization Of Bean Roots Has No Effect On Planmentioning
confidence: 99%